А. Кримський і П. Загребельний про історію України: лінгвокультурний діалог - Голікова, Н. (Культура слова, 2021)
У статті проведено зіставний аналіз наукового дискурсу А. Кримського та художнього дискурсу П. Загребельного, у яких зафіксовано лінгвософію історії України середини ХVІ ст. Акцентовано увагу на мовних особливостях праці «Історія Туреччини» А. Кримського та на історичному романі «Роксолана» П. Загребельного – ключових творах, у яких вербалізовано Україну періоду султанування Сулеймана І Пишного. Визначено основні «точки перетину» індивідуально-авторських наративів, окреслено історіографічний та інтерсеміотичний простори досліджуваних текстів, що сформовані на основі цитації та фольклоризації. Простежено своєрідність ідіолектів А. Кримського та П. Загребельного відповідно до функціонально-стильових норм української літературної мови. Зіставлено сукупність стилістем, релевантних для мовного «портретування» текстоцентричних постатей – Сулеймана й Роксолани – у науковому дискурсі А. Кримського та в художньому дискурсі П. Загребельного. Проаналізовано лінгвостилістичні засоби оприявнення мислеобразу «Роксолана» – історичного символу України в мові однойменного роману П. Загребельного. Зауважено, що «доба жіночого султанату» актуальна як для історії Туреччини, так і для історії України і що вивчення специфіки концептуалізації та вербалізації жіночих образів в різножанрових історичних текстах є перспективним для сучасної лінгвоукраїністики. The article presents a comparative analysis of the cognitivesemantic structure of the linguoculturema «Ukraine» in the scientific discourse of A. Krymskyi and in the artistic discourse of P. Zagrebelnyi. Emphasis is placed on the linguistic features of A. Krymskyi’s History of Turkey and P. Zagrebelnyi’s historical novel Roksolana, in which Ukraine is immersed in the life of the Ottoman Empire in the mid-16th century – the period of sultanate of Suleiman Pyshnyi. The main «points of intersection» of individual authorial narratives on the personosphere and historiography of Ukraine are determined, the intersemiotic space of the researched texts, formed on the basis of citation and folklorization, is outlined. The common plot-content segment of the analyzed historical texts is revealed, the linguistic-stylistic means of its representation are characterized. The specific features of the idiolects of A. Krymskyi and P. Zagrebelnyi in accordance with the functional and stylistic norms of the Ukrainian literary language are traced. The set of stylists relevant for the linguistic «portrait» of text-centric figures – Suleiman and Roxolana – in the scientific discourse of A. Krymskyi and in the artistic discourse of P. Zagrebelnyi is analyzed. The peculiarities of verbalization of the thought image «Roksolana» – a historical symbol of Ukraine in the language of the novel of the same name by P. Zagrebelnyi have been studied. It is noted that the «era of the female sultanate» is relevant for both the history of Turkey and the history of Ukraine and that the study of the problem of addressing female images in historical texts of various genres and styles is promising for a number of linguistic disciplines. It is concluded that in the scientific work «History of Turkey» by A. Krymskyi and in the historical novel «Roksolana» by P. Zagrebelnyi presents objective and subjective directions of conceptualization of thought «Ukraine», which occupies an important place in the national-linguistic picture of the world.